Neurokinin-1 receptor, a new modulator of lymphangiogenesis in obese-asthma phenotype - Ramalho, Renata (2020)
Aims Obesity and asthma are widely prevalent and associated disorders. Recent studies of our group revealed that Substance P (SP) is involved in pathophysiology of obese-asthma phenotype in mice through its selective NK1 receptor (NK1-R). Lymphangiogenesis is impaired in asthma and obesity, and SP activates contractile and inflammatory pathways in lymphatics. Our aim was to study whether NK1-R expression was involved in lymphangiogenesis on visceral (VAT) and subcutaneous (SAT) adipose tissues and in the lungs, in obese-allergen sensitized mice. Main methods Diet-induced obese and ovalbumin (OVA)-sensitized Balb/c mice were treated with a selective NK1-R antagonist (CJ 12,255, Pfizer Inc., USA) or placebo. Lymphatic structures (LYVE-1 +) and NK1-R expression were analyzed by immunohistochemistry. A semi-quantitative score methodology was used for NK1-R expression. Key findings Obesity and allergen-sensitization together increased the number of LYVE-1 + lymphatics in VAT and decreased it in SAT and lungs. NK1-R was mainly expressed on adipocyte membranes of VAT, blood vessel areas of SAT, and in lung epithelium. Obesity and allergen-sensitization combined increased the expression of NK1-R in VAT, SAT and lungs. NK1-R antagonist treatment reversed the effects observed in lymphangiogenesis in those tissues. Significance The obese-asthma phenotype in mice is accompanied by increased expression of NK1-R on adipose tissues and lung epithelium, reflecting that SP released during inflammation may act directly on these tissues. Blocking NK1-R affects lymphangiogenesis, implying a role of SP, with opposite physiological consequences in VAT, and in SAT and lungs. Our results provide a clue for a novel SP role in the obese-asthma phenotype.